Decomposição de resíduos e ciclagem de nutrientes de plantas de coberturas na entressafra soja-trigo em clima subtropical - Nespolo, Sabrina (2023)
There is growing concern about the health of the soil and the environment, associated the need to produce food in large quantities and of high quality. That way, some producers adopt the Direct Planting System, which in the southern region of Brazil, manySometimes, cover crops are used prior to the winter crop. Thus, the analysis of decomposition of plant residues and the release of nutrients, is important for the choosing the most suitable ground cover. The objective of the study is to analyze the speed of decomposition of dry matter and the availability of nutrients, Nitrogen (N), Phosphorus (P) and Potassium (K) from Forage Turnip, from Rx 210® Fall Cover Crop Mix + Vetch and soybean crop residues (Fallow). An experiment was implemented on a property private in Vitorino – PR, with two autumn ground covers, Forage turnip and Mix of coverage Rx 210® + vetch and an area in Fallow (residues from soybean crops). To the At the end of the crop cycle, plant residues from the areas were collected and placed in litterbags, which were weighed and analyzed at eight different times: 15, 30, 45, 65, 85, 105, 135 and 165 days after their deposition. The experiment was conducted at experimental design randomized blocks, with six blocks and three treatments (coverages soil), totaling 18 experimental units. In the statistical analysis, the days after litter bag deposition as repeated measurements over time. Therefore, the experimente was composed by the combination of three cover crop residues x eight times, totaling 24 treatments. The data were analyzed using analysis of variance of repeated measurements over time, followed by the adjustment of non-linear equations for the variables in time and for the unfolding of the interaction; and Tukey test ( = 5%) for comparison of soil covers. Mix Rx 210® + vetch showed decomposition and release of intermediate nutrients in relation to forage turnip and fallow. The treatments presented ram rapid decomposition of dry matter and similar up to 90 days after deposition of the dry matter in the soil. N release was similar to the MS decomposition curve, being two factors related to the C/N ratio of the coverage; The behavior of soybean fallow and Mix Rx 210® + vetch is similar in terms of P release. The forage turnip has slower release. K was the nutrient with the fastest release, especially in Turnip forager. Mix Rx 210® + vetch and turnip showed higher average release of N. However, they did not differ from each other or from soybean fallow, regarding the average release of P.